2021
DOI: 10.7759/cureus.13384
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Kaposi Sarcoma Precipitated by Anti-Tumor Necrosis Factor-Alpha (Anti-TNF-α) Therapy

Abstract: Kaposi sarcoma (KS) is a vascular neoplasm caused by human gammaherpesvirus 8 (HHV-8). Four subtypes of KS are described: classic (Mediterranean), epidemic (acquired immunodeficiency syndrome (AIDS)-associated), endemic (sub-Saharan Africa), and iatrogenic. Iatrogenic KS due to tumor necrosis factor-alpha (TNF-α) inhibitor therapy is particularly rare. A 66-year-old female with a history of seropositive rheumatoid arthritis (RA) presented with a skin lesion on her right second toe. Diagnosed with RA four years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…7,8 Iatrogenic CS due to TNF-α inhibitor therapy is rare. 9 Although some meta-analyses of clinical trial data found an increased risk of cancer using TNF-α inhibitor, observational data, especially from registries, generally did not confirm these findings. 10 Overall, there is evidence that TNF-α inhibitors do not increase the risk of most solid tumors, except for some skin cancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8 Iatrogenic CS due to TNF-α inhibitor therapy is rare. 9 Although some meta-analyses of clinical trial data found an increased risk of cancer using TNF-α inhibitor, observational data, especially from registries, generally did not confirm these findings. 10 Overall, there is evidence that TNF-α inhibitors do not increase the risk of most solid tumors, except for some skin cancers.…”
Section: Discussionmentioning
confidence: 99%
“…16 To our knowledge, five KS cases were identified with the use of infliximab, three cases with adalimumab, one with golimumab, and one with certolizumab pegol. 9,[17][18][19][20][21][22][23][24][25][26] unclear and should be addressed by appropriate studies. In most of the cases, KS was notably localized to the skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mariappan и соавт. [28] сообщили о случае гистологически подтвержденной ятрогенной СК, развившейся у 66-летней женщины с серопозитивным РА без ВИЧ-инфекции через 2 мес после начала терапии АДА. Ранее пациентка без эффекта получала лечение МТ, ГКХ и ЭТЦ.…”
Section: терапия иврз при вичunclassified
“…Sunduğumuz olgu steroid, metotreksat ve tofacitinib kullanımı sonucu gelişen ancak steroid ve metotreksat kesilmesine rağmen gerilemeyen, sadece tofacitinib kullanımı sonucu iatrojenik Kaposi sarkomu gelişen yurtiçinden bildirilen ilk olgudur. İnfliksimab kullanımı sonrası beş olgu, adalimumab üç, golimumab bir, vedolizumab iki, sertolizumaba bağlı bir adet olgu bildirilmiştir [6][7][8] . Ayrıca diabetes mellitus, immunsupresyon ve steroid kullanımı sonucu dermatofit enfeksiyonlarının daha yaygın ve şiddetli seyretmesine neden olmaktadır 9 .…”
Section: Introductionunclassified